Overtime Working and Contract Efficiency - Robert A. Hart; Yue Ma (Institute for the Study of Labor (IZA), 2013)
We present a wage-hours contract designed to minimize costly job turnover given investments in on the job training combined with firm and worker information asymmetries. It may be optimal for the parties to work 'long hours' remunerated at premium rates for guaranteed overtime hours. Based on British plant and machine operatives, we test three predictions. First, trained workers with longer job tenure are more likely to work overtime. Second, hourly overtime pay exceeds the value of marginal product while the basic hourly wage is less than the value of marginal product. Third, the basic hourly wage is negatively related to the overtime premium.
Keywords: J41; J33; 330; paid overtime; wage-hours contract; plant and machine operatives